A comprehensive review of the anti-arthritic and anti-inflammatory potentials of the balloon vine plant (Cardiospermum halicacabum L.) - Vinotha, S. (Tropical Plant Research, 2025)
Arthritis is one of the many common rheumatic conditions that affect joints and connective tissues throughout the body all over the world. This condition is more prevalent in women than in men, and it's frequently associated with ageing. Treatment is often based on age, linked factors, risk factors, and symptoms. Medicinal herbs are used widely in indigenous medicine, particularly in underdeveloped nations, to cure arthritis. It is a climbing plant that belongs to the Sapindaceae (soapberry family) and has a wide range of therapeutic uses. Currently, herbal remedies and dietary supplements derived from the Cardiospermum halicacabum plant are utilized in Sri Lanka to treat arthritis. The researcher conducted this type of study to demonstrate Cardiospermum halicacabum's anti-inflammatory and anti-arthritic properties. Scientific studies relevant to comprehensive reviews, in vitro and in vivo, with clinical studies were used to conduct the current study. Based on scientific investigations, the present review confirmed that it has anti-inflammatory, anti-arthritic, and analgesic possessions. It also plays an imperative role in the treatment of arthritis and some inflammatory disorders. This review article will be very helpful to the established indication for the special anti-inflammatory and anti-arthritic properties of the balloon vine plant.
Keywords: Anti-arthritic; Anti-inflammatory; Balloon vine; Cardiospermum halicacabum; Review